The local skin cellular immune response determines the clinical outcome of sarcoptic mange in Iberian ibex (Capra pyrenaica) - Valldeperes, Marta; Granados, José Enrique; Pérez, Valentín; López-Olvera, Jorge Ramón; Ráez-Bravo, Arián; Fandos, Paulino; Pérez, Jesús M.; Mentaberre, Gregorio; Tampach, Stefania; Soriguer, Ramón C.; Espinosa, José (Frontiers in Veterinary Science, 2023)
Sarcoptic mange, caused by Sarcoptes scabiei, is a disease relevant for wildlife conservation and management. Its severity depends on host local skin immune response, which is largely unknown in Iberian ibex (Capra pyrenaica), a mountain ungulate dramatically affected by mange. In this species, the clinical outcome of sarcoptic mange varies among individuals, and the local immune response could be key to control the infestation. This study aims to characterize the local cellular immune response and its relationship with clinical outcome. Fourteen Iberian ibexes were experimentally infested with S. scabiei and six more served as controls. Clinical signs were monitored and skin biopsies were collected from the withers at 26, 46, and 103 days post-infection (dpi). The presence and distribution of macrophages (including M1 and M2 phenotypes), T lymphocytes, B lymphocytes, plasma cells, and interleukine 10 were quantitatively evaluated using immunohistochemical techniques. An inflammatory infiltrate that decreased significantly from 26 to 103 dpi was observed in all the infested ibexes. The predominant inflammatory cell population in the skin of the mangy ibexes was formed by macrophages (mainly the M2 phenotype) followed by T lymphocytes, with lower numbers of B lymphocytes and plasma cells. Three clinical courses were identified: total recovery, partial recovery, and terminal stage. The inflammatory infiltrates were less pronounced in the fully recovered ibexes than in those that progressed to the terminal stage throughout the study. The results suggest an exacerbated but effective Th1-type cellular immune response controlling mange in Iberian ibex. Furthermore, the local immune response appears to determine the variability of the clinical responses to S. scabiei infestation in this species. This first report of the progression of local skin immune cell is relevant not only for individuals, but also for population management and conservation.